Early Modern Catholicism and Its Historiography - Geraerts, Jaap (Church history and religious culture, 2017)
This article analyses several key developments within the recent historiography on early modern Catholicism. It charts the transformation from church history to religious history, the use of important concepts such as identity and memory, and the focus on transnational and minority Catholicism, showing that over the last couple of decades the field of early modern Catholicism has been enriched and revitalized by cultural historical methods and concepts. This change of perspective and approach caused that the study of early modern Catholicism has become less isolated and more embedded in the wider study of the early modern period in general.